The Effect of Giving Rome Beauty Apple Juice (Malus sylvestris Mill.) Toward Fasting Blood Glucose Levels of Patients with Type 2 Diabetes Mellitus - Dara Azahra; Saraheni; Rif’atul Amini; Joko Cahyono (JURNAL RISET GIZI, 2026)
Background: Type 2 diabetes mellitus is a serious health problem with an increasing number of cases. This increase in prevalence necessitates prevention and control efforts to help stabilize blood glucose levels. Rome Beauty apples are known to contain antidiabetic compounds, such as pectin fiber, flavonoids, and vitamin C, which play a role in increasing insulin sensitivity and regulating blood glucose levels. Objective: This study aims to analyze the effect of Rome Beauty apple juice on blood glucose levels in patients with type 2 diabetes mellitus in the working area of the Karang Asam Samarinda Community Health Center. Method: This study used a pre-experimental design with a one-group pretest-posttest design. The intervention consisted of 150 grams of apple juice blended with water to make 250 mL, administered once a day for seven days. A sample of 18 respondents was selected using purposive sampling. Primary data included fasting blood glucose levels measured three times: before the intervention (pretest on day 0), after 3 days of intervention (control on day 4), and after 7 days of intervention (posttest on day 8), as well as a respondent characteristics questionnaire. Data analysis was conducted using SPSS software with the Wilcoxon test. Results: The results showed that the mean fasting blood glucose (FBG) level before the intervention was 170.89 ± 61.82 mg/dL and decreased to 150.72 ± 41.21 mg/dL after the intervention. The Wilcoxon test produced a p-value of 0.021 (p < 0.05), indicating a significant effect of Rome Beauty apple juice consumption on fasting blood glucose levels in patients with type 2 diabetes mellitus. Conclusion: The seven-day Rome Beauty apple juice intervention had a significant effect on fasting blood glucose levels in patients with type 2 diabetes mellitus.